Developing trauma-responsive approaches to student discipline : a guide to trauma-informed practice in PreK-12 schools - Eggleston, Kirk; Green, Erinn J.; Abel, Shawn; Poe, Stephanie; Shakeshaft, Charol (New York, NY : Routledge, 2021)
Building on comprehensive research conducted in US schools, this accessible volume offers an effective model of school leadership to develop and implement school-wide, trauma-responsive approaches to student discipline. Recognizing that challenging student behaviours are often rooted in early experiences of trauma, the volume builds on a model from the Substance Abuse and Mental Health Services Administration (SAMHSA) to walk readers through the processes of realizing, recognizing, responding to, and resisting the impacts of trauma in school contexts. Research and interviews model an educational reform process and explain how a range of differentiated interventions including Positive Behaviour Interventions and Supports (PBIS), social-emotional learning (SEL), restorative justice, and family engagement can be used to boost student resilience and pro-social behaviour. Practical steps are supported by current theory, resources, and stories of implementation from superintendents, principals, and teachers. This text will benefit school leaders, teachers, and counsellors with an interest in restorative student discipline, emotional and behavioural difficulties in young people, and PreK-12 education more broadly. Those interested in school psychology, trauma studies, and trauma counselling with children and adolescents will also benefit from the volume.
"Routledge focus"
OCLC-licensed vendor bibliographic record.
Keywords: School discipline; EDUCATION / Educational Policy & Reform / General